IMPLEMENTATION OF REACT STRATEGY TO DEVELOP MATHEMATICAL REPRESENTATION, REASONING, AND DISPOSITION ABILITY - Delsika Pramata Sari; Darhim Darhim (Journal on Mathematics Education, 2020)
The purpose of this study was to describe how to implement the REACT strategy to develop students’ mathematical representation, reasoning, and disposition ability. This research was a descriptive study with a qualitative approach. The subject of this study was grade 8 junior high school student in Bandung. Data collection techniques in this study with observations, interviews, and documentation. Based on data analysis results, it could be concluded that REACT strategies can be applied to develop a mathematical representation, reasoning, and disposition ability that engages students actively. Implementation of the REACT strategy runs smoothly and gets enthusiastic responses from students. The application of REACT strategies should be undertaken sustainably so that the learning objectives can be achieved by integrating various mathematical skills that were capable.